2019
DOI: 10.1111/jocd.13088
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study: Autologous platelet‐rich plasma used in a topical cream for facial rejuvenation

Abstract: The basic human need to look young has led to many concepts in facial rejuvenation. One such concept is the adaptation of platelet-rich plasma (PRP) for dermatologic uses. 1 PRP was originally developed to improve healing in orthopedic and dental surgery, but is now used in plastic surgery via injection for wound healing and hair growth. 2,3 The next horizon is the adaptation of PRP for topical uses in cosmetic formulations.Platelets are composed of a cytoskeleton and intracellular structures such as glycogen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
1
0
3
Order By: Relevance
“…These factors not only aid in clotting but also drive angiogenesis and promote tissue repair and regeneration [10]. Multiple authors have shown that topical application or intradermal injection of PRP and its growth factors produce favorable cutaneous changes: clinical (restores its vitality, increases its thickness, recovers its elastic consistency, improves blood circulation, increases its smoothness, decreases its wrinkles and improves their appearance) [2,10,11] histopathological (increases the number of fibroblasts, collagen fibers and blood vessel basement membranes) [2,10,12] immunohistochemical (improves collagen expression type I, III and IV) [13][14][15] and the genetic material (through the polymerase chain reaction expression of three target genes, such as: collagen IA, matrix metalloproteinase gene 1 and protein rich in proline of keratinocytes) [13,14]. PRP has been used as an adjunct to multiple skin rejuvenation treatments (lipotransference, laser, peeling, lifting).…”
Section: Discussionmentioning
confidence: 99%
“…These factors not only aid in clotting but also drive angiogenesis and promote tissue repair and regeneration [10]. Multiple authors have shown that topical application or intradermal injection of PRP and its growth factors produce favorable cutaneous changes: clinical (restores its vitality, increases its thickness, recovers its elastic consistency, improves blood circulation, increases its smoothness, decreases its wrinkles and improves their appearance) [2,10,11] histopathological (increases the number of fibroblasts, collagen fibers and blood vessel basement membranes) [2,10,12] immunohistochemical (improves collagen expression type I, III and IV) [13][14][15] and the genetic material (through the polymerase chain reaction expression of three target genes, such as: collagen IA, matrix metalloproteinase gene 1 and protein rich in proline of keratinocytes) [13,14]. PRP has been used as an adjunct to multiple skin rejuvenation treatments (lipotransference, laser, peeling, lifting).…”
Section: Discussionmentioning
confidence: 99%
“…Initial search retrieved 539 articles and from these, 523 were excluded based on title, abstract and exclusion criteria. A total of 16 articles were included in the review,[ 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 ] with an aggregate of 586 participants [ Table 1 ]. Among the 16 articles, in 10 studies (62.5%), PRP was injected in monotherapy, in five studies (31.2%), PRP was topically applied following ablative laser treatment (CO 2 or erbium), microneedling or electroporation and in one study (6.3%) PRP was injected in conjunction with autologous fat.…”
Section: R Esultsmentioning
confidence: 99%
“…Dengan konsentrasi platelet di atas rata-rata dan penuh komplemen faktor pembekuan, PRP dapat berkontribusi meningkatkan penyembuhan (jumlah platelet normal 150.000-350.000/μL). 7,18,19 PRP digunakan di berbagai cabang ilmu kedokteran seperti estetika, bedah plastik, ortopedi, kedokteran gigi, trauma dan penyembuhan luka, oftalmologi, serta gastroenterologi sebagai bagian dari kedokteran regeneratif. Kedokteran regeneratif merupakan bidang penelitian dan aplikasi klinis secara interdisipliner yang berfokus pada perbaikan, penggantian, atau regenerasi sel, jaringan, atau organ untuk mengembalikan fungsi yang rusak.…”
Section: E Kasiunclassified
“…Sentrifugasi pertama (hard spin) memisahkan Selanjutnya ditambahkan trombin atau kalsium klorida sebagai aktivator platelet. 18,21 Trombin dan kalsium klorida merupakan penginduksi agregasi yang berfungsi mengaktifkan platelet dan menstimulasi degranulasi, mengakibatkan pelepasan faktor pertumbuhan. Studi terkini menemukan bahwa penggunaan agregator tersebut tidak diperlukan karena saat pemberian, platelet secara otomatis dilepaskan dan siap untuk berfungsi.…”
Section: E Kasiunclassified